Influence of genotype on PCSK9-lipids association in cerebrospinal fluid and serum of patients in the Alzheimer's disease continuum. - Papotti, Bianca; Palumbo, Marcella; Adorni, Maria Pia; Elviri, Lisa; Chiari, Annalisa; Tondelli, Manuela; Bedin, Roberta; Baldelli, Enrica; Lancellotti, Giulia; Lupo, Maria Giovanna; Ferri, Nicola; Bertolotti, Marco; et al. (J Alzheimers Dis, 2024)
BACKGROUND: Alterations in factors involved in cholesterol homeostasis are critical in Alzheimer's disease (AD), but the stage of occurrence, their specific association, and a possible relationship with the genotype are not clarified. OBJECTIVE: We aimed to quantify and correlate specific lipid factors in patients with different degrees of cognitive decline, namely patients with AD and patients with mild cognitive impairment due to AD (MCI-AD), carriers or non-carriers of the genotype. METHODS: We evaluated Proprotein Convertase Subtilisin/Kexin type 9 (PCSK9), cholesterol and the oxidative metabolites 24-, 25-, 27-hydroxycholesterol (HC) in the cerebrospinal fluid (CSF) and serum of AD (n = 28) and MCI-AD (n = 27) patients. RESULTS: CSF and serum PCSK9 and lipids were similar, except for higher serum PCSK9 and triglycerides in MCI-AD compared to AD. In CSF, AD carriers showed higher PCSK9 and 24-HC (+61.3%,  = 0.027 and +32.7%,  = 0.037), compared to non-carriers. There was a negative association between CSF PCSK9 and 27-HC in AD (r = -0.444,  = 0.049) and, exclusively among AD carriers, a negative association between CSF PCSK9 and 24-HC (r = -0.786,  = 0.028). A positive correlation was observed between CSF and serum PCSK9 in AD (r = 0.520,  = 0.004), driven by carriers (r = 0.544,  = 0.038), suggesting PCSK9 exchange between brain and periphery. A positive correlation was detected between serum and CSF 27-HC (r = 0.465,  = 0.039) in AD. None of these results were found in MCI-AD patients. CONCLUSIONS: PCSK9 and 24-HC might be specific markers of ApoE4-associated lipid alterations in AD, possibly contributing to clinical progression in the AD continuum.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Apolipoprotein E4; Biomarkers; Cholesterol; Cognitive Dysfunction; Female; Genotype; Humans; Lipids; Male; Middle Aged; Proprotein Convertase 9

Increased PCSK9 Cerebrospinal Fluid Concentrations in Alzheimer's Disease. - Zimetti, Francesca; Caffarra, Paolo; Ronda, Nicoletta; Favari, Elda; Adorni, Maria Pia; Zanotti, Ilaria; Bernini, Franco; Barocco, Federica; Spallazzi, Marco; Galimberti, Daniela; Ricci, Chiara; Ruscica, Massimiliano; et al. (J Alzheimers Dis, 2017)
BACKGROUND: Alzheimer's disease (AD) has been associated with dysregulation of brain cholesterol trafficking and abnormal production of apolipoprotein E isoform 4 (apoE4). Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a protein present in serum and cerebrospinal fluid (CSF) degrading the low-density lipoprotein receptor (LDLr) and other apoE-binding receptors involved in neuron cholesterol uptake. The role of PCSK9 in AD is controversial. OBJECTIVE: We compared PCSK9 levels in CSF of AD patients and non-AD controls and looked at correlations with CSF total apoE and apoE4. METHODS: CSF from AD (n = 30) and from age and sex-matched non-AD patients (n = 30) was collected by lumbar puncture for routine diagnosis. CSF PCSK9, total apoE, and apoE4 levels were measured by ELISA. AD patients showed the typical CSF neurobiomarker pattern (decreased Aβ42 and increased tau and phospho-tau) and impaired cognitive performances, as indicated by the scores of the Mini-Mental State Examination test. RESULTS: PCSK9 levels in CSF were higher in AD than in non-AD subjects (+1.45 fold; p = 0.0049). CSF total apoE concentrations did not differ between the two groups, while apoE4 levels were higher in AD subjects (+3.34 fold; p = 0.0068). Considering all samples, a significant positive correlation was found between PCSK9 and apoE4 (r = 0.4409; p = 0.0006). PCSK9 levels were higher in APOE ɛ4 carriers, reaching statistical significance in the AD group (+1.45 fold; p = 0.0454). CONCLUSION: These results report for the first time an alteration of CSF PCSK9 levels in AD and suggest a pathophysiological link between PCSK9, apoE4, and AD.